Location of Retrograde Changes in the Nervous System Following Unilateral Sympathectomy in Sheep - Welento, Janusz (Acta Agraria Debreceniensis, 2002)
Following unilateral right sympathectomy in sheep, it was found on the strength of retrograde changes in the anterior cervical ganglion, the stellate ganglion and neuromeres Th1 – Th4 that there exists a connection between the cervical sympathetic trunk and the vagus nerve.